Hemolytic anemia in a case of SARS CoV2 infection without respiratory involvement: a new dimension of COVID-19 - Pandey, Saurabh; Gupta, Manoj Kumar; Butta, Shristi; Rai, Priyanka (International Journal of Research in Medical Sciences, 2020)
Severe acute respiratory syndrome coronavirus-2 (SARS CoV-2) infection is a predominantly respiratory illness with variable organ involvement. Hematological changes are an important manifestation and anemia is usually autoimmune in origin. It is easily identifiable and treatable complication. In absence of tell tail sign of COVID-19 infection high index of suspicion is required with prompt testing. Our patient presented as case of autoimmune hemolytic anemia with no evidence of COVID-19 infection and tested after ruling out common causes in Indian setting. He responded to steroid therapy and viral clearance.